INTERNALISASI NILAI-NILAI DALAM MEMBENTUK PROFIL PELAJAR PANCASILA DI MA MANHALUL MA’ARIF DAREK - ASTUTI, NANIK NIA PUJI; ZUBAIR, MUH; ALQADRI, BAGDAWANSYAH; MUSTARI, MOHAMMAD (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This study aims to describe the internalization of values ??in forming the Strengthening of the Pancasila Student Profile Program (P5) at MA. Manhalul Ma'arif Darek and also describe the obstacles faced by PPKn teachers in forming the Strengthening of the Pancasila Student Profile Program (P5) at MA. Manhalul Ma'arif Darek. This study uses qualitative research with a descriptive type. The informants in this study were the vice principal of student affairs, the principal, PPKN teachers and also students. The data collection techniques in this study used interview, observation and documentation techniques. The results of this study are that MA Manhalul Ma'arif darek has not implemented the independent curriculum, but indicators in the Strengthening of the Pancasila Student Profile Program (P5) have been implemented such as Believing and being devoted to God Almighty implemented through Tahsin, imtaq and also the study of the mentor's father, global diversity implemented through morning assembly activities and tolerance, Independent implemented through discipline and Muhadaroh, mutual cooperation implemented through clean Sunday activities and making school wall magazines, critical reasoning implemented through activities to create poetry and speech texts and creative implemented through cooking practice activities and also making school organizational charts. ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan internalisasi nilai-nilai dalam membentuk Penguatan Program Profil Pelajar Pancasila (P5) di MA. Manhalul Ma’arif Darek dan juga mendeskripsikan kendala-kendala yang dihadapi guru PPKn dalam membentuk Penguatan Program Profil Pelajar pancasila (P5) di MA. Manhalul Ma’arif Darek. Penelitian ini menggunakan penelitian kualitatif dengan jenis deskriptif. Informan dalam penelitian ini adalah waka kesiswaan, kepala sekolah, guru ppkn dan juga siswa. Adapun teknik pengumpulan data dalam penelitian ini menggunakan teknik wawancara, observasi dan dokumentasi. Hasil dari penelitian ini adalah MA Manhalul Ma’arif darek belum secara menyeluruh menerapkan kurikulum merdeka namun indikator pada Penguatan Program Profil Pelajar Pancasila (P5) sudah dijalankan seperti Beriman dan bertaqwa kepada Tuhan Yang Maha Esa diterapkan melalui kegiatan Tahsin, imtaq dan juga pengajian abah pembina, berkebinekaan global diterapkan melalui kegiatan apel pagi dan sikap toleransi, Mandiri diterapkan melalui sikap disiplin dan Muhadaroh, gotong royong diterapkan melalui kegiatan ahad bersih dan membuat mading sekolah, bernalar kritis diterapkan melalui kegiatan membuat teks puisi dan pidato dan kreatif diterapkan melalui kegiatan praktik memasak dan juga membuat bagan organisasi sekolah.